POTENSI PENGEMBANGAN SUMBER DAYA MANUSIA PENYULUH PERTANIAN DI KABUPATEN SIGI - Pricylia Chintya Dewi Buntuang; Harnida Wahyuni Adda (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
Agriculture is one of very important sectors supporting regional economy.  Therefore, it is crucial for the regional government to develop existing potential agricultural sectors in its region.  The research aimed at analyzing and descripting human resources potency of agricultural extension in Sigi district.  The method of this research was designed qualitatively and analyzed descriptively aimed at depicting the research results entirely based on data that linked to the potency of agricultural human resources in Sigi district. The population of this research was purposively determined from the agricultural extension workers.  Primary and secondary data were collected through observations, interviews, and researching documents related to the research.  The human resources in Sigi district are potential in providing agricultural extension to farmers although not yet optimal due to their limited knowledge and education.  This condition should lead to comprehensive training for the workers in order to support their tasks as the extension workers.The research also showed that another problem faced by them is limited accessibility resulted from lack of infrastructure and this affects the performance of the workers in the field. Keywords: Agriculture, farmer, and human resources.